Study on the Prevalence of type 2 diabetes Mellitus among women population of Bangalore, India: Understanding the Prevalence and Risk Factors of Type 2 Diabetes Mellitus in the Female Population of Bangalore, India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Today, type 2 diabetes mellitus is the most common form of the disease in India, and theprevalence is rising at an alarming rate (T2DM). The fast urbanization of the suburbs is to blame for theincreased incidence of diabetes mellitus. Increasing urbanization, ageing populations, dietary shifts,decreased physical activity, and other bad habits are all leading to an increase in diabetes mellituscases. The most effective therapy for decreasing complications and early mortality in women with T2DMis to develop and maintain good lifestyle practices. Bengaluru's female population is still lacking data onthe prevalence of T2DM and its related variables. In light of this, researchers in Bengaluru, Karnataka, setout to find out how common diabetes mellitus is among women and whether or not it's linked to any of anumber of risk factors. Among women under the age of 40, diabetes was found to be widespread, and itwas shown to be prevalent among all three types of workers. BMI more than 25 and WHR greater than0.85 were reported in the majority of diabetics, both of which raise the possibility of diabetes developing.Most of them had a good genetic profile and did not engage in physical activity or adhere to any foodregimen. There was a strong link discovered between being older, having a lower level of education,being obese, having a larger waist circumference, and having diabetes. Women having a history ofdiabetes and other risk factors were shown to have a higher chance of getting the disease.